Application of LDRA TestBed in CTCS2-200C Expansion Unit Software Testing - Zhou Yongjian; Fan Ming; Zhang Miao; Zhao Dongxu (机车电传动)
The application of LDRA TestBed and CTCS2-200C expansion unit was introduced. Using CTCS2-200C as an example,through the static and dynamic testing of the software, with reference to the 50128:2011 EN standard, the verification and validationactivities in the entire software development life cycle were improved, and the risk of the software was reduced.